Experimental Handling Challenges Result in Minor Changes in the Phagocytic Capacity and Transcriptome of Head-Kidney Cells of the Salmonid Fish Coregonus maraena - Martorell-Ribera, Joan; Koczan, Dirk; Tindara Venuto, Marzia; Viergutz, Torsten; Brunner, Ronald M.; Goldammer, Tom; Gimsa, Ulrike; Rebl, Alexander (Frontiers in Veterinary Science, 2022)
Aquaculture management involves regular handling procedures, which have been reported to evoke stress responses in farmed fish. We compiled an extensive list of published parameters that indicate most likely handling-induced physiological deviations from the norm. As these parameters are based almost exclusively on studies in rainbow trout and Atlantic salmon, we conducted a handling-challenge experiment with maraena whitefish (Coregonus maraena). This salmonid fish was sampled either 3 h or 24 h after a single one-minute handling or after 10 d of daily repeated one-minute handling. Although cortisol levels were strongly elevated in some individuals 3 h after the single handling challenge, these elevations were not significant for the challenged cohort compared to the control cohort. The phagocytic capacity of myeloid head-kidney cells stimulated with fluorophore-labelled, inactivated Aeromonas salmonicida was significantly decreased in maraena whitefish 3 h after the handling challenge relative to control fish. Microarray analysis of head kidney samples from challenged and control fish revealed 12 and 70 differentially expressed genes, respectively, 3 h and 24 h after the single handling episode and only 12 differentially expressed genes after 10 d of repeated daily handling. The identified genes were assigned to numerous stress- and immune-relevant functional pathways, including “glucocorticoid receptor signaling” (3 h post challenge) “HIF1A signaling” (24 h post challenge) or “complement system” (10 d of repeated challenge). Our data reveal the tight interconnection of immune and stress pathways in the head kidney of maraena whitefish and suggest several parameters that had been previously found regulated in other tissues of handling-stressed rainbow trout and may indicate compromised health and welfare of maraena whitefish in aquaculture.